Peningkatan Minat Belajar Siswa pada Pembelajaran Matematika Media Cube Net di Kelas IV SDN Dukuh Kupang II-489 Surabaya - Kayyisah Kayyisah; Lusy Tunik Muharlisiani; Mei Puspita Dewi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study was motivated by the low interest in learning of fourth grade students of SDN Dukuh Kupang II Surabaya. The objectives of this study are to: (1) describe the steps to increase students' interest in learning by using cube net learning media; (2) increase the interest in learning of grade IV students in the 2023/2024 academic year through the use of cube net learning media. This research is a type of Classroom Action Research (PTK) with research subjects totalling 28 fourth grade students of SDN Dukuh Kupang II Surabaya in the 2023/2024 academic year. The instruments used were questionnaires and observation sheets, while the data analysis technique used was quantitative descriptive analysis. The results showed that: (1) The steps to increase interest in learning by using cube net learning media have been successfully implemented through various activities such as material delivery, group learning, data collection, working on student worksheets, and group presentations; (2) The application of cube net learning media is effective in increasing student interest in learning, seen from the increase in the average value of student interest in learning from the initial condition of 65.53 (less) to 75.37 in cycle I and 81.8 (high) in cycle II.